Politik penegakan hak asasi manusia pada masa transisi d Indonesia - Halili, Halili (Jurnal Civics: Media Kajian Kewarganegaraan, 2016)
This article was aimed at (1) discovering and constructing the political dynamics in formulating the Law of the Court of Human Rights; (2) analyzing its implication on the future of politic of Human Rights in Indonesia. This essay was a result of content analysis research with qualitative-comparative approach. The finding showed that (1) substantively, the formulation of Law No. 26 Year 2000 on Human Rights Court has fundamental weaknesses such as a partial adaptation of The Roma Statute, the course of human rights court was constructed weak by stating its authority only on investigation, whereas attorney General's Office authority on investigation lacks of detail prescription, deleting the responsibility of command such as those on the Rome Statute, etc. A lot of lacks indicate that the law was only an instrument of transitional authority. The "˜toothless' law indicates the victory of the old regime in political battlement and tension with the new regime in reformation era. The politicization of handling of human rights violation before the release of the law of Court on which the Representative People Council has authority to propose but the decision maker is the President by Presidential Decree. 2) the political dynamic has an implication on two long term situations, hoarding impunity and the crises of human rights values.